KONTEKSTUALISASI PEMAHAMAN HADIS TENTANG TRANSAKSI JUAL BELI KONTEMPORER - Pohan, Adawiyana (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Online buying and selling  is now increasingly prevalent, what else are the sites used to make online buying and selling transactions  more and more diverse. However, as we know that in the online buying and selling system,  the  products offered are only in the form of explanations of the specifications of goods and images that cannot be guaranteed to be correct. For this reason, as a buyer, it is very important to find out the truth whether the item you want to buy is appropriate or not. Online buying and selling is very helpful for people to facilitate buying and selling activities.  In this study, it discusses the quality of sanad and matan Hadith about buying and selling transactions, as well as how to understand hadith about buying and selling transactions textually and contextually. This study aims to find out how the quality of hadith about buying and selling transactions. Then how is the hadith understanding of buying and selling transactions textually and contextually. This research method is included in the  category of qualitative methods, by searching for sources or library studies, and using the maudu'i method, namely collecting Hadith that are in line with the Hadiths of buying and selling transactions. In the process of collecting data, takhrij al-Hadith is carried out, namely tracing the Hadith to the original source. The result of the dropshipping system research is an online buying and selling transaction, where the seller does not have the goods if there is an order from the buyer later, they just need to buy it to the manufacturer or owner of the goods, and the goods will be sent directly to consumers. Dropshipping buying and selling transactions according to scholars are allowed and the law is legal, including from the category of buying and selling contracts, namely, greeting contracts and in making transactions must be more careful so as not to occur fraud.